2019
DOI: 10.3791/60114
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Colloidal Lead Halide Perovskite Nanoplatelets via Ligand-Assisted Reprecipitation

Abstract: In this work, we demonstrate a facile method for colloidal lead halide perovskite nanoplatelet synthesis (Chemical formula: L 2 [ABX 3 ] n-1 BX 4 , L: butylammonium and octylammonium, A: methylammonium or formamidinium, B: lead, X: bromide and iodide, n: number of [BX 6 ] 4octahedral layers in the direction of nanoplatelet thickness) via ligand-assisted reprecipitation. Individual perovskite precursor solutions are prepared by dissolving each nanoplatelet constituent salt in N,N-dimethylformamide (DMF), which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…Colloidal Mn-doped organic–inorganic hybrid perovskite nanoplatelets were synthesized via the ligand-assisted reprecipitation method ,, with some modifications (see Figure S1 and the Methods/Experimental section for more details). To control the fraction of Mn 2+ in the resulting nanoplatelets, the ratio between manganese ions and lead ions in the precursor solution mixture was varied.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Colloidal Mn-doped organic–inorganic hybrid perovskite nanoplatelets were synthesized via the ligand-assisted reprecipitation method ,, with some modifications (see Figure S1 and the Methods/Experimental section for more details). To control the fraction of Mn 2+ in the resulting nanoplatelets, the ratio between manganese ions and lead ions in the precursor solution mixture was varied.…”
Section: Resultsmentioning
confidence: 99%
“…Like perovskite quantum dots, , perovskite nanoplatelets have been shown to exhibit bright emission without the need for a passivating inorganic shell. , Furthermore, perovskite nanoplatelets are very strongly confined in one dimensionin contrast to 0D perovskite nanocrystals, which are typically larger ,, than the exciton Bohr radius ,,,, and, therefore, weakly confined . Strong quantum- and dielectric-confinement of monodisperse nanoplatelets ,,,,, induces a large blue shift of the excitonic absorption and emission features by up to 0.7 eV , compared to those of bulk perovskites and a significant enhancement of the exciton binding energy, reaching magnitudes up to several hundred millielectron volts. , Since early reports in 2015, , significant improvements in perovskite nanoplatelets have been demonstrated, including photoluminescence quantum yield (PLQY), , tunability, and stability. , In addition, solution processability combined with anisotropic distribution of dipole moments, , large absorption coefficients, and the potential for effective strain relaxation and effective doping make colloidal perovskite nanoplatelets even more promising for next-generation applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Colloidal perovskite NPls were initially identified as a side product of MAPbBr 3 NC synthesis, but very quickly the ability to precisely control thickness was reported. ,,, Following these initial works, subsequent efforts focused on developing refined synthetic protocols for NPls with well-controlled thicknesses and improved material properties. For instance, the color of emission can be tuned by varying thickness and composition. ,,, Also, reports on the tunability of surface-capping ligands, ranging from short ligands for optimal charge transport behavior to long and functionalized ligands for enhanced stability, have highlighted the possibility of optimizing surface properties of NPls for specific applications. It has also been reported that the lateral dimension of NPls, which may affect electronic transport in NPl optoelectronic devices, can be tuned from tens of nanometers ,,,,,, to several micrometers ,,, without loss of quantum confinement in the vertical direction.…”
Section: Shape-controlled Synthesis Of Mhp Ncsmentioning
confidence: 99%
“…Summary of the range of PL peaks reported for different kinds of halide perovskite NPls of different thicknesses in terms of the number of monolayers (ML). 1 ML 403-405 [25,31] 396-406 [25,28,[39][40][41] 398-403 [25,39] 513 [25] 513-527 [25,39,[42][43][44][45] 513 [25,39] 2 ML 433-435 [25,29,31,46,47] 431-440 [25,28,40,41,48,49] 434-440 559-565 [25,50] 574-584 [25,32,39,[42][43][44][45]50] 575-580 [25,39,[50][51][52] 3 ML 449-462 [25,29,31,46,47,53] 445-456…”
Section: General Synthesis Methodsmentioning
confidence: 99%